Can someone show me step by step?
a person who buys goods and services
a business owner who sells clothes
a farmer who sells his crops
Answer: Second option is correct.
Step-by-step explanation:
Since we have ask that
Consumer refers to those person who used to consume things like purchase goods and services for personal use.
Someone who studies economics are known as economists they are not consumers, they are known for their study of economics.
A business owner who sells clothes can be known as traders or merchants or business man but they do not consider as consumers as they don't buy goods and services but they provide all of these.
A farmer who sells his crops are known as producers instead of consumers.
So, Second option is correct.
A person who buys good and services is known as consumer.
Answer:
$3300 at 4%
$11700 at 7%
Step-by-step explanation:
Total investment = $15000
Total simple interest on investment = $951
Investment A:
Rate = 4% =0.04
Investment B:
Rate = 7% =0.07
Simple interest (S. I) = principal * rate * time
(S. I on investment A + S. I on investment B)
Let principal amount in investment A = A
principal amount in investment B = B
(A * 0.04 * 1) + (B * 0.07 * 1) = $951
0.04A + 0.07B = $951 - - - - (1)
A + B = $15000 - - - - (2)
from (2)
A = 15000 - B
Substitute A = 15000 - B into (1)
0.04(15000 - B) + 0.07B = 951
600 - 0.04B + 0.07B = 951
600 + 0.03B = 951
0.03B = 951 - 600
0.03B = 351
B = 351 / 0.03
B = $11700
From (2)
A + B = $15000
A + $11700 = $15000
A = $(15000 - 11700)
A = $3300
Answer: 9ft
Step-by-step explanation:
9 x 6 = 54 ÷ 6 = 9
Answer:
The decrease is exponential.
Step-by-step explanation:
An exponential decrease is something like:
f(x) = A*(r)^x with 0 < r < 1
A linear decrease is something like:
g(x) = -a*x + b with a > 0
First ai general formula.
If you have a quantity Q, decreased by an X%, the new quantity will be:
New Quantity = Q - Q*(X%/100%)
Now let's look at the question:
Suppose that the original price of the computer component is K
And the price as a function of the year is P(y)
Then we know that, in the year zero, the price is K.
P(0) = K
One year after, the price decreases by 2.25%
Then:
P(1) = K - K*(2.25%/100%) = K*(1 - 0.0225)
After another year, we will have another decrease of 2.25%
Then:
P(2) = K*(1 - 0.0225) - K*(1 - 0.0225)*(2.25%/100%)
P(2) = K*(1 - 0.0225)*(1 - 0.0225) = K*(1 - 0.0225)^2
We already can see the pattern, we can expect that in the year y, the price of the component will be:
P(y) = K*(1 - 0.0225)^y
This clearly is an exponential decrease.